Validation of the Compassion Fatigue Short Scale among Chinese medical workers and firefighters: a cross-sectional study. Issue 6 (30th June 2016) - Sun, Binghai; Hu, Mengna; Yu, Shitian; Jiang, Yiru; Lou, Baona
Abstract : Objectives: To examine the psychometric properties of the Chinese version of the C-Compassion Fatigue (CF)-Short Scale among 4 independent samples of Chinese emergency workers (medical workers and firefighters). Design: Cross-sectional. Setting: 6 hospitals in Zhejiang Province and 12 fire stations in Shanghai. Participants: Emergency workers (medical and firefighters) were consecutively recruited and divided into 4 groups: the MW1 group (medical workers, n=167), the FF1 group (firefighters, n=157), the MW2 group (medical workers, n=265) and the FF2 group (firefighters, n=231). Interventions: All patients completed the C-CF-Short Scale to identify factors associated with compassion fatigue. The MW1 and FF1 groups were used for the exploratory analyses. The MW2 and FF2 groups were used for the confirmatory factor analyses. Primary and secondary outcome measures: Factor loading, correlations with previously validated questionnaires (the Ego-Resiliency Scale, the Social Support Questionnaire and the Job Pressure Scale) and Cronbach's α coefficient were tested for each factor. Results: The C-CF-Short Scale demonstrated excellent construct validity and good internal consistency. Specifically, the results of exploratory factor analyses in the MW1 and FF1 groups showed that secondary trauma and job burnout were associated with compassion fatigue in these emergency workers. The confirmatory factor analyses in the MW2 and FF2 groups indicated that all the fit indices of the 2-factor model were satisfactory. Finally, the Cronbach's α coefficient of each factor was excellent. Conclusions: The findings suggest that the C-CF-Short Scale has good psychometric properties and can be applied to study Chinese emergency workers.